Serum levels of soluble CD26 and CD30 and their clinical significance in patients with rheumatoid arthritis - Ulusoy, Hasan; Kamanli, Ayhan; Ilhan, Necip; Kuru, Omer; Arslan, Sule; Alkan, Gokhan; Ozgocmen, Salih (Springer Heidelberg, 2012)
The aim of this study was to assess serum levels and clinical significance of soluble CD26 (sCD26) and soluble CD30 (sCD30) in patients with rheumatoid arthritis (RA). Forty-eight patients with RA and 30 healthy controls were enrolled. Serum sCD26 and sCD30 levels were measured using ELISA. Serum sCD26 levels were significantly lower (P = 0.011), whereas sCD30 levels were higher (P = 0.008) in patients with RA than controls. Serum levels of sCD30 correlated significantly with clinical and laboratory parameters of disease activity like erythrocyte sedimentation rate, C-reactive protein, disease activity scores-28 and health assessment questionnaire score; however, sCD26 levels did not correlate any of these activity parameters. These results suggest that serum sCD30 levels increased and correlated significantly with disease activity, indicating a novel follow-up parameter in RA. Serum levels of sCD26 may be lessen but not related to disease activity in RA.
Keywords: Rheumatoid arthritis; Disease activity; CD26; CD30